(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: To the best of our knowledge, no strict criteria for estimating the probability of glaucomatous progression have been reported. Purpose: To investigate the interrelationship between corneoscleral rigidity, corneal thickness, and target IOP in patients with stage 1 or 2 of unstabilized primary open-angle glaucoma (POAG). Materials and Methods: Patients underwent routine eye examination for glaucoma. In addition, Pascal dynamic contour tonometry and ocular blood flow tonography were performed, corneoscleral rigidity was determined, and target IOP was calculated. Results: Patients with unstabilized POAG were divided into two groups. Group 1 involved 9 patients (8 patients and 1 patient with stage 1 and stage 2 of POAG, respectively) whose tonometer IOP was higher than true IOP, and Group 2 involved 14 patients (1 patient and 13 patients with stage 1 and stage 2 of POAG, respectively) whose tonometer IOP was lower than true IOP. In the former group, corneoscleral rigidity values were one order of magnitude higher than those in the latter group. It is likely that the corneoscleral rigidity in eyes with stage 1 of unstabilized POAG is substantially higher than that in eyes with stage 2 of unstabilized POAG. It was noted that patients with stage 2 of POAG had low central corneal thickness of 460 μm to 515 μm. It was found that a comparatively low target IOP of 12.7 mm Hg to 13.0 mm Hg was required for patients with a rather high corneoscleral rigidity (-2.3 mm Hg, -0.7 mm Hg, 3.1 mm Hg, 6.8 mm Hg, 6.9 mm Hg), and a comparatively high target IOP of 14.2 mm Hg to 14.6 mm Hg was required for patients with lower corneoscleral rigidity (-5.5 mm Hg, -3.2 mm Hg, -1.5 mm Hg, -4.9 mm Hg, 0.8 mm Hg). Conclusion: Absolute values of target pressure required for stabilization of POAG in patients with high corneoscleral rigidity are 10.7% lower than those for patients with low corneoscleral rigidity, and this difference is statistically significant.